IMPROVING THE STUDENT'S ACTIVENESS IN MATHEMATICS LEARNING THROUGH COOPERATIVE LEARNING MODEL OF ASSISTED INDIVIDUALIZATION TEAM - Annisa Nurohmawati; Aris Thobirin (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
This research background is active less of VIII grade SMP Muhammadiyah 2 Kalasan Sleman on the semester academic year 2016/2017 in the learning mathematics. This research aims to increase students' activeness in the learning of mathematics using cooperative learning model type Team assisted individualization (TAI) class VIII Junior High School (SMP) Muhammadiyah 2 Kalasan, Sleman semester academic even year 2016/2017. This research is a class act. The setting used is a class VIII SMP Muhammadiyah 2 Kalasan, district Sleman totaling 28 students. The study was conducted in two cycles of the first cycle and the second cycle, each cycle consisting of three meetings. The first cycle and the second cycle using cooperative learning model type TAI. Data collected by observation using observation sheet student learning activeness, and interviews. Analysis instrument using content validity. Analysis of the data used is descriptive qualitative. The result showed that using cooperative learning model type TAI can increase students' activeness in mathematics learning in class VIII student of SMP Muhammadiyah 2 Kalasan the school year 2016/2017. This is evident from the observation of students' learning activities in each cycle. The average percentage of student activity observation on the first cycle, 54,16%, reached sufficient criteria. On the second cycle, it increased to 63,77% that reached both criteria. From interviews with students showed a positive response to the students learning activeness.